**Let us consider the circuit in Figure 27a.**

Converting voltage sources to the current sources we achieve the scheme in Figure 27b. All the current sources are form one equivalent current source* I*, where:

Thus:

$E=ZI=\frac{\sum _{k=1{Y}_{k}{Z}_{k}}^{n}}{\sum _{k=1{Y}_{k}}^{n}}$This means that n parallel voltage sources can be replaced with one current source or voltage source.

Current in the external network is the following:

${I}_{n+1}=I\frac{Z}{Z+{Z}_{n+1}}=\frac{E}{Z+{Z}_{n+1}}$Voltage between two nodes can be found the following way:

$U=I\left(\begin{array}{c}Z{Z}_{n+1}\\ Z+{Z}_{n+1}\end{array}\right)=I\frac{1}{\sum _{k=1}^{n+1}{Y}_{k}}=\frac{\sum _{k=1}^{n}{E}_{k}{Y}_{k}}{\sum _{k=1}^{n+1}{Y}_{k}}$